2019
DOI: 10.3390/antibiotics8020034
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity in Compounds from the Australian Desert Plant Eremophila alternifolia with Potency Against Cryptococcus spp.

Abstract: Plant metabolites that have shown activity against bacteria and/or environmental fungi represent valuable leads for the identification and development of novel drugs against clinically important human pathogenic fungi. Plants from the genus Eremophila were highly valued in traditional Australian Aboriginal medicinal practices, and E. alternifolia was the most prized among them. As antibacterial activity of extracts from E. alternifolia has been documented, this study addresses the question whether there is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Leubethanol from Leucophyllum frutescens is active against multi-drug-resistant tuberculosis ( Molina-Salinas et al ., 2011 ), biflorin from Capraria biflora and Eremophila neglecta has both anti-tumor ( Carvalho et al ., 2013 ) and anti-microbial ( Ndi et al ., 2007a ) properties, and microthecaline A from Eremophila microtheca is active against malaria ( Kumar et al ., 2018 ). While relatively few have been identified in other genera, the Eremophila genus is especially rich in these anti-microbial compounds ( Ndi et al ., 2007b ; Anakok et al ., 2012 ; Barnes et al ., 2013 ; Mon et al ., 2015 ; Algreiby et al ., 2018 ; Hossain et al ., 2019 ) and at least three are found in the Myoporum genus ( Aminimoghadamfarouj and Nematollahi, 2017 ). Given their promise in therapeutic applications, there has been a substantial effort to devise total chemical syntheses ( Best and Wege, 1986 ; Lu et al ., 2013 ; Yu et al ., 2016 ; R. Kumar et al ., 2017 ; Tenneti et al ., 2018 ; Penjarla et al ., 2019 ) as an alternative to extraction and purification from natural sources ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leubethanol from Leucophyllum frutescens is active against multi-drug-resistant tuberculosis ( Molina-Salinas et al ., 2011 ), biflorin from Capraria biflora and Eremophila neglecta has both anti-tumor ( Carvalho et al ., 2013 ) and anti-microbial ( Ndi et al ., 2007a ) properties, and microthecaline A from Eremophila microtheca is active against malaria ( Kumar et al ., 2018 ). While relatively few have been identified in other genera, the Eremophila genus is especially rich in these anti-microbial compounds ( Ndi et al ., 2007b ; Anakok et al ., 2012 ; Barnes et al ., 2013 ; Mon et al ., 2015 ; Algreiby et al ., 2018 ; Hossain et al ., 2019 ) and at least three are found in the Myoporum genus ( Aminimoghadamfarouj and Nematollahi, 2017 ). Given their promise in therapeutic applications, there has been a substantial effort to devise total chemical syntheses ( Best and Wege, 1986 ; Lu et al ., 2013 ; Yu et al ., 2016 ; R. Kumar et al ., 2017 ; Tenneti et al ., 2018 ; Penjarla et al ., 2019 ) as an alternative to extraction and purification from natural sources ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study reported that Eremophila alternifolia leaf extracts have substantial antifungal and antibacterial activity against multiple pathogens [13]. That study also demonstrated that the extracts inhibited several important cellular pathways and disrupted membrane integrity in Gram-positive bacterial species.…”
Section: Antibacterial Activitymentioning
confidence: 71%
“…Some of those studies have already been summarised in the preceding section. Additionally, a recent study screened E. alternifolia leaf extracts and isolated compounds for antiviral activity and reported substantial activity [13]. The authors tested the extract and isolated compounds using disk diffusion and broth microdilution assays against ten clinically relevant yeast and mould species.…”
Section: Antifungal and Antiviral Propertiesmentioning
confidence: 99%
“…Hossain et al ( 44 ) conducted a study to evaluate the antifungal activity of five isolated compounds from Eremophila alternifolia against eight yeast and two mold species. This study is like ours in relation to the method used to determine the MIC of the compounds (in triplicate); for this reason, it was used as a preliminary screening technique for antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%